Mechanical Properties of Thulium-doped Bismuth Borotellurite Glass via Nanoindentation for Lead-Free Radiation Shielding Application - Mat Rusni, Nur Arina; Amat, Azuraida; Wan Yusoff, Wan Yusmawati; Abdul Manaf, Nor Azlian; Ahmad, Nurazlin (International Journal of Integrated Engineering, 2024)
Commercially, lead-based glasses are used in industry as transparent radiation shielding material due to their durability. However, lead toxicity could cause detrimental health issues to humans. Thus, in this study, a new composition of thulium-doped bismuth borotellurite glass was fabricated via melt-and-quench technique. The effect of bismuth oxide (Bi2O3) on the physical, structural, and mechanical properties of the glass was investigated. Glass with 0.25 mol% of Bi2O3 has the highest density. However, the oxygen packing density (OPD) of glass with 0.15 mol% of Bi2O3 is higher than 0.25 mol% of Bi2O3. This is due to a high number of non-bridging oxygen (NBOs) in 0.25 mol% of Bi2O3 glass structure. The bonds that are present in the glass structure were verified by Fourier Transform Infrared Spectroscopy (FTIR) analysis. Then, the mechanical properties were investigated by nanoindentation test with Berkovich indenter. Comparing the mechanical properties of indented glass samples, 0.15Bi glass projected the best mechanical durability since it provides the highest hardness and reduced elastic modulus value. Also, the low plastic work and optimal elastic work make 0.15Bi glass resilient to stress. Thus, the 0.15Bi glass is deemed as the best glass sample for high mechanical strength radiation shielding glass. This lead-free radiation shielding glass does not pose harmful effects to humans.